Tracing the Representation of Consumer Culture in the Home Sweet Loan Novel by Almira Bastari - Nina Agustina; Tristanti Apriyani; Jang Dongyun (COMMICAST, 2025)
Consumer culture increasingly shapes modern society by redefining consumption as a marker of identity, status, and social distinction rather than merely fulfilling material needs. This phenomenon is critically represented in Home Sweet Loan by Almira Bastari, a contemporary Indonesian novel that portrays urban life immersed in symbolic consumption. This study aims to analyze the representation of consumer culture in the novel through Jean Baudrillard’s theoretical framework, particularly the concepts of sign value, simulacra, and hyperreality. Employing a qualitative descriptive approach, the research uses repeated close readings of the text to collect data in the form of narrative excerpts, which are then systematically categorized and analyzed using content analysis techniques. The findings reveal that consumer culture in Home Sweet Loan operates through the dominance of sign value, where luxury goods function as symbols of social identity and status. Simulacra emerge in the portrayal of urban spaces and lifestyles that prioritize appearance over lived reality, while hyperreality is manifested through glamorous images of success that obscure socioeconomic disparities. These dynamics demonstrate how consumption shapes interpersonal relationships and self-perception within a materialistic urban society. This study contributes to literary and cultural studies by extending Baudrillard’s consumer culture theory to contemporary Indonesian popular literature, highlighting literature’s role in reflecting and critiquing modern consumerist ideology. The study concludes that Home Sweet Loan not only mirrors consumer culture but also invites critical reflection on the social consequences of identity construction through consumption.